Optimization of solar powered air conditioning system using alternating Peltier power supply - Salman, Mustafa Mohammed; Mahdi, Mahmoud Mustafa; Ahmed, Majida Khalil (Institute of Advanced Engineering and Science, 2024)
Solar-powered thermoelectric air conditioning systems offer distinct advantages over traditional cooling methods, including thermal comfort, absence of moving parts, and eco-friendliness as they operate on solar energy. Despite these benefits, they exhibit a lower coefficient of performance (COP) compared to conventional systems. In this study, a solar-powered thermoelectric air conditioning system based on the Peltier effect was experimentally investigated in Baghdad during September (39 °C to 32 °C). The system was designed to cool a small 1 m³ test room. The six Peltier modules were divided into groups, each powered by a different electrical source with varying ON/OFF intervals. The highest COP achieved was 0.649, with an optimal outlet air temperature of 22-23 °C and a 20 minute switching cycle. Notably, the inlet air velocity directly influenced COP and outgoing air temperature. The study also indicated improved performance at reduced air flow, making Peltier air coolers ideal for hot regions.